Target detection and tracking using phase-array radar - Sng, Larissa (2018)
This report, based on the Final Year Project, Target Detection and Tracking Using Phased Array Radar, aims to explore the replicabilities of the radar system using MATLAB (r2017). It aims to discuss and detail basic radar concepts, which will then be implemented in a radar simulation. Both radar fundamentals and signal processing will be covered in this report. Several scenarios will be taken into consideration when running the simulations, from single targets to multiple targets, as well as both stationary and moving targets. User input will be included in the simulations, together with a PPI plot which would serve as a radar display.